Translanguaging Done by The English Teachers in ELT in Affirmation Area of Kabupaten Sikka - Nimanuho, Maria Salvatrix B B; Padmadewi, Ni Nyoman; Swandana, I Wayan (Riviera Publishing, 2025)
Recent studies have analyzed and dissected that translanguaging is an emersion phenomenon applied recently in English pedagogy, as one of the bridges for the English Educators. Those studies bring about the good of translanguaging applications, which take different places and subjects. Hence, this study continues to examine the production of translanguaging, specifically in places where vernacular still exists and influences the dialect of the locals, also aims to find out whether or not the existence automatically affects the translanguaging process in ELT. The data were taken from two senior high schools, SMA Negeri 1 Maumere and SMA Negeri 1 Waigete located in a place categorized as 3T (Tertinggal/underdeveloped, Terluar/outermost, Terdepan/most front) also known as affirmation areas where the land languages are spoken more than the Indonesian as the national language. The participants are two English Teachers from each school and the students under their teaching. The data collection was done by conducting semi-structured interviews with the teachers and observation. Both results from the observation and interview were qualitatively analyzed. The results reveal that during the process of ELT, teachers switch the language by using Indonesian with local dialect and sometimes even using the vernacular, especially in the more rural affirmation place. It implies that recognizing and embracing the fluid use of multiple languages in educational settings can enhance cognitive flexibility, and cultural understanding, thereby promoting a more holistic approach to learning.